2016
DOI: 10.1021/jacs.6b05917
|View full text |Cite
|
Sign up to set email alerts
|

Consistent View of Polypeptide Chain Expansion in Chemical Denaturants from Multiple Experimental Methods

Abstract: There has been a long-standing controversy regarding the effect of chemical denaturants on the dimensions of unfolded and intrinsically disordered proteins: A wide range of experimental techniques suggest that polypeptide chains expand with increasing denaturant concentration, but several studies using small-angle X-ray scattering (SAXS) reported no such increase of the radius of gyration (Rg). This inconsistency challenges our current understanding of the mechanism of chemical denaturants, which are widely em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

38
283
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 179 publications
(323 citation statements)
references
References 105 publications
38
283
2
Order By: Relevance
“…With increasing GdmCl concentration, the unfolded state is increasingly populated, and its peak shifts from higher to lower transfer efficiency (Fig. 2B), reflecting chain expansion, as observed previously for protein L (37-39) and many other proteins (23,40,41).…”
Section: Resultssupporting
confidence: 79%
“…With increasing GdmCl concentration, the unfolded state is increasingly populated, and its peak shifts from higher to lower transfer efficiency (Fig. 2B), reflecting chain expansion, as observed previously for protein L (37-39) and many other proteins (23,40,41).…”
Section: Resultssupporting
confidence: 79%
“…This artifact is widely acknowledged, and it has been proposed that using a self-avoiding walk (SAW) model is a better description for protein chains at high denaturant concentrations, where they are typically close to the EV limit [28][29][30][31] . In a recent study of an unfolded and an intrinsically disordered protein in chemical denaturants, we indeed found that applying a SAW model to FRET data at high denaturant concentrations led to inferred average properties ( and ) close to those obtained by a global analysis integrating both FRET and SAXS data in an ensemble description based on atomistic simulations, while the result from using a Gaussian chain overestimated these properties 4 . On the other hand, at low denaturant concentrations, and inferred from a Gaussian chain model were closer to those from a global analysis than the SAW model.…”
Section: Introductionmentioning
confidence: 52%
“…Studying the structure, dynamics and function of these disordered polypeptide chains, as well as other disordered biopolymers, requires new experimental methods, and new methods of interpreting the data, since they are inherently averaged over a broad ensemble of heteropolymer configurations [2][3][4] . Examples of experiments which can help address this challenge include: nuclear magnetic resonance (NMR), which can provide short-range structural information via scalar coupling, chemical shift and NOE data 5 , as well as long-range information by paramagnetic relaxation enhancement (PRE) measurements 6 , and global information from diffusion coefficient measurements; light-scattering 7 and two-focus FCS 4,8 , which also yield diffusion coefficients and hence hydrodynamic radius; small-angle X-ray (or neutron) scattering (SAXS or SANS), which directly gives information on inter-and intramolecular pair distance distributions 9 ; and Förster resonance energy transfer (FRET), in particular single-molecule FRET, which probes the distribution of distances between pairs of chromophore labels attached to the molecule of interest, as well as the associated dynamics, and often enables structured and unstructured subpopulations to be separated 10,11 . Obtaining as detailed as possible a picture of the disordered ensemble would ideally combine information from all of these experiments, if available.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results favor the former, but the extent of collapse can of course depend on the solution conditions and the net charge of the chain (53,82). Resolving this controversy will require further concerted efforts involving a direct comparison of the different methods, either using time-resolved ensemble methods or proteins that remain unfolded even at low denaturant concentrations (83,84).…”
Section: Discussionmentioning
confidence: 68%